URGENSI BUDAYA SINTUWU MAROSO SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (STUDI MULTISITUS DI SMA NEGERI 1, 2, 3 DAN 4 KABUPATEN POSO) - Makmur, Makmur; Ismail, Ibrahim; Hasanah, Uswatun (Dahzain Nur, 2024)
Sintuwu Maroso is a local culture of the Pamona community or tribe, which has been practiced since their settlement in the Poso Regency. Additionally, Sintuwu Maroso culture aligns with Islamic teachings due to its Islamic educational values, namely Tuwu Mombetubunuka (mutual respect), Tuwu Mombepatuwu (mutual sustenance/not causing harm to each other), Tuwu Siwagi (mutual support/helping others fulfill their needs), Tuwu Simpande Raya (understanding/tolerance), Tuwu Sintuwu Raya (upholding unity and solidarity), Tuwu Mombepomawo (mutual love), and Tuwu Molinuwu (productive life/not being lazy in seeking sustenance). The research problem posed in this study is whether Sintuwu Maroso culture embodies Islamic educational values that can be used as a learning medium for Islamic Religious Education and Character Education in schools. The aim of this research is to uncover Islamic educational values within Sintuwu Maroso culture as a means of teaching Islamic Religious Education and Character Education. The research method employed is qualitative in the form of descriptive field research, utilizing data collection techniques such as observation, interviews, and documentation. The findings reveal that there are seven Islamic educational values within Sintuwu Maroso culture that can be utilized as a medium for teaching these values in Islamic Religious Education and Character Education subjects. These values include Tuwu Mombepatuwu (mutual sustenance), Tuwu Siwagi (mutual support), Tuwu Simpande Raya (understanding), Tuwu Sintuwu Raya (unity in diversity), Tuwu Mombepomawo (mutual love), and Tuwu Molinuwu (productive life). All these educational values within Sintuwu Maroso culture are rooted in the Qur’an and Hadith. In conclusion, Sintuwu Maroso culture represents Islamic Culture Education and serves as an investment in multicultural education.